Development of a competition assay to assess the in vitro fitness of dengue virus serotypes using an optimized serotype-specific qRT-PCR - Anne-Fleur Griffon; Loeïza Rault; Clément Tanvet; Etienne Simon-Lorière; Myrielle Dupont-Rouzeyrol; Catherine Inizan (PLoS ONE, 2025)
Background Comparing the in vitro fitness of dengue virus (DENV) isolates is a pivotal approach to assess the contribution of DENV strains’ replicative fitness to epidemiological contexts, including serotype replacements. Competition assays are the gold standard to compare the in vitro replicative fitness of viral strains. Implementing competition assays between DENV serotypes requires an experimental setup and an appropriate read-out to quantify the viral progeny of strains belonging to different serotypes. Methods In the current study, we optimized an existing serotyping qRT-PCR by adapting primer/probe design and multiplexing the serotype-specific qRT-PCR reactions, allowing to accurately detect and quantify all four DENV serotypes. We next developed an in vitro competition assay to compare the replicative fitness of two DENV serotypes in the human hepatic cell line HuH7. Findings The qRT-PCR was specific, and had a limit of detection below 7.52, 1.19, 3.48 and 1.36 genome copies/µL, an efficiency of 1.993, 1.975, 1.902, 1.898 and a linearity (R²) of 0.99975, 0.99975, 0.99850, 0.99965 for DENV-1, −2, −3 and −4, respectively. Challenge of this multiplex serotype-specific qRT-PCR on mixes of viral supernatants containing known concentrations of strains from two serotypes evidenced an accurate quantification of the amount of genome copies of each serotype. Quantification of the viral progeny of each serotype in the inoculum and the supernatant of competition assays using the serotype-specific multiplex qRT-PCR unveiled an enrichment of the supernatant in DENV-1 genome copies, uncovering the enhanced replicative fitness of this DENV-1 isolate. Conclusions This optimized qRT-PCR combined with a relevant cellular model allowed to accurately quantify the viral progeny of two DENV strains belonging to two different serotypes in a competition assay, allowing to determine which strain had a replicative advantage. This reliable experimental setup is adaptable to the comparative study of the replicative fitness of any DENV serotypes.